2019
DOI: 10.2166/wcc.2019.242
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall analysis for rain-fed farming in the Great Rift Valley Basins of Ethiopia

Abstract: Rainfall is the most important source of water for crop production in Ethiopia. However, its temporal and spatial variability is leading to serious food shortages and insecurity in the country. This study was aimed at investigating the characteristics of selected agroclimatic variables over the great Rift Valley regions of Ethiopia. Long term (1981–2010) climate data were analyzed for 17 stations selected based on agroecology representation. Selected descriptors for climate variability and the Mann–Kendall tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…In some other areas, bimodal rainfall pattern in which the highest rainfall is received in the months of April (long season) and October (short season) was identified. The second pattern recognized in the study area is the monomodal pattern of rainfall with a long Kiremt season that stretches from March through November (Ademe et al, 2020). The basins receive a total annual rainfall ranging from 538 mm in the northern lowlands of the Awash basin to as high as 1494 mm in south and southwestern parts of the basin.…”
Section: Results and Discussion 31 Spatial Variations Of Annual And Seasonal Precipitation In The Grvbmentioning
confidence: 92%
See 2 more Smart Citations
“…In some other areas, bimodal rainfall pattern in which the highest rainfall is received in the months of April (long season) and October (short season) was identified. The second pattern recognized in the study area is the monomodal pattern of rainfall with a long Kiremt season that stretches from March through November (Ademe et al, 2020). The basins receive a total annual rainfall ranging from 538 mm in the northern lowlands of the Awash basin to as high as 1494 mm in south and southwestern parts of the basin.…”
Section: Results and Discussion 31 Spatial Variations Of Annual And Seasonal Precipitation In The Grvbmentioning
confidence: 92%
“…The selection ensured balanced representation of the major agroecology with data records of no more than 10% missing value (Seleshi and Zanke, 2004). Data quality have been ensured and published in Ademe et al (2020). Projected changes in rainfall and temperature were analyzed based on 8 combinations of 4 Global Climate Model (GCMs) (CNRM-CM5, EC-EARTH, HadGEM2-ES and MPI-ESM-LR), dynamically downscaled by 1 Regional Climate Models (RCM) (RCA4) and 2 Representative Concentration Pathways (RCPs) (RCP4.5 and RCP8.5).…”
Section: Climate Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…and "stdry" in Kirundo and 21.5 and 20.3 days for "start" and "stdry" in Muyinga. High standard deviations of onset date of seasons lead to a misunderstanding of climate dynamics and, as a result, decisions about planting and related activities will be made at high risk (Ademe et al, 2019). The onset of the growing season may be associated with the northward/southward movement of the ITCZ and the Congo air mass which are subjected also to variability in year scale (Mugalavai et al, 2008;Ininda, 1994).…”
Section: Onset Cessation and Length Of Growing Periodmentioning
confidence: 99%
“…Trend and variability analysis of rainfall and temperature series is necessary for agriculture production, energy production, drinking water supply, and management and utilization of resources (Bekele et al, 2016). Trend and variability analysis in precipitation and temperature series have been investigated by many researchers in Ethiopia, Ademe et al(2019) for the Great Rift Valley Basins of Ethiopia, Bekele et al(2016) for Keleta watershed of Awash River Basin, Muluneh and Biazin(2015) in the Central Rift Valley of Ethiopia, Mengistu et al(2014) in the Upper Blue Nile River Basin of Ethiopia, Tekle and Tadele(2014) in Bilate watershed of Ethiopian rift valley, Kassie et al(2013) in the Central Rift Valley of Ethiopia, Setegn et al(2011) in Lake Tana Basin and Abdo et al(2009) in Gilgel Abay Catchment of Abay Basin, The reports agree that, temperature showed an increasing trend and except for few stations, no significant trend in the annual rainfall pattern was observed for the majority of stations studied and most of the studies indicated there is a variability in rainfall. Tibebe et al (2019) indicated that there is a variability of rainfall and streamflow whereas an increasing trend of streamflow was observed in most of the stations within Awash river basin.…”
Section: Introductionmentioning
confidence: 99%